Peran Guru Kelas dalam Pembentukan Karakter Religius Siswa Kelas IV Sekolah Dasar Negeri Pandean 2 - Aisyah, Siti Nur; Permata, Santy Dinar; Mashuri, Anwas (Civiliza Publishing, Indonesia., 2023)
This study aims to determine the role of teachers in the formation of religious character of fourth grade students at SDN Pandean 2. The religious character of fourth grade students is already apparent when students do activities at school. The formation of students' religious character is important, as an educator, teachers need to carry out their role in motivating students, guiding students and being good role models for students as an effort to form student character. The method used in this study is qualitative research. The data collection technique used is to compile all data obtained from observation, interviews and documentation. Data analysis techniques in this study consist of data collection, data condensation, and data presentation. The results of the study indicate that the role of teachers as educators in the formation of religious character has been implemented well. This can be seen when teachers are able to be good role models, teachers have motivated students not only in terms of enthusiasm for learning but also motivating students to behave well, and teachers have broad insight to strengthen their role as educators. The religious character of students at SDN Pandean 2 is trained through habituation activities that are carried out, such as memorizing letters, praying in congregation, and directing students to have an attitude of tolerance.